Pemodelan dan Simulasi Photovoltaic Menggunakan Pendekatan Model Tiga Diode - Usman; Ahmad Rosyid Idris; Sofyan; Irfan Syamsuddin (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2020)
Photovoltaic (PV) performance measurement requires a conditioned environment, which are conditions of solar radiation and temperature standard, thus, a special equipment is required. A simple way to do this is by modeling the PV. The method used to describe the characteristics of PV is equalizing the maximum power of model with the maximum power from datasheet, which is implemented in MATLAB. The simulation results show that the difference between ????????????,???? and ????????????,???? is 0.000314 W and the average absolute error of current, compared to measurement, is 2.159%. The I-V curves obtained in this model are also very identical to the I-V curves using two diode approach or one diode model. The simulation results of this model are also compared to the same model, using the MRFO, SFO, COA, WOA, SA, and GA algorithms, which shows high similarities. I-V curves are strongly influenced by the constants ????, ????????, and ????????. The constant ???????? affects the curvature of the I-V curve, to be precise the curvature at ????????, ????????. Whereas ???????? affects the curvature of the I-V curve before ????????, ???????? and ???????? after ????????, ????????.